THE EFFECT OF E-FILING SERVICE QUALITY ON TAXPAYER SATISFACTION IN SUBMITTING ANNUAL SPT AT KPP PRATAMA MEDAN BELAWAN - Lili Amelia; Ferizaldi; Nursanjaya; Muryali; Arinanda (RADJA PUBLIKA, 2025)
This study discusses the effect of e-Filing service quality on taxpayer satisfaction at KPP Pratama Medan Belawan. The author identified problems in service that need to be improved, especially through improving the quality of employees, infrastructure, and technology. These improvements aim to make it easier for taxpayers to carry out their obligations. The method used in this study is quantitative with a correlational approach. In this study, the theory used as the basis is the ServQual theory by Zeithaml et al regarding the quality of e-filing services, as well as the theory put forward by Mohamed regarding taxpayer satisfaction. The population studied included all taxpayers in Medan Belawan District who utilized e-Filing services, with a sample size of 96 people. Data analysis was carried out using simple linear regression analysis (t-test) with the help of SPSS version 22 software, to determine the extent to which the quality of e-Filing services influences taxpayer satisfaction in submitting annual tax returns. The results of the study indicate that the quality of e-Filing services has a significant effect on taxpayer satisfaction. This is evidenced by the results of the partial test (t-test), where the Sig. value. obtained (6.808>1.984) at a significance level of 0.05. In addition, the results of the determination coefficient test (R²) showed a value of 0.323 (32.3%), which means that the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. Thus, e-Filing services at KPP Pratama Medan Belawan must continue to be improved so that taxpayers increasingly trust the electronic taxation system and can increase their satisfaction in submitting Annual Tax Returns.